PEMBIASAAN KEDISIPLINAN BELAJAR MELALUI DARING PADA SISWA KELAS X DI MADRASAH ALIYAH YASTI SEKURA TAHUN PELAJARAN 2021-2022 - Pariono; H. Mujahidin, Mauizatul Hasanah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research originated from seeing the phenomenon that occurred in schools, there were some teachers who were lacking in disciplining the learning administration, therefore the principal tried to improve teacher professionalism. This study aims to obtain clear information about: 1) Principal management plans to improve professionalism of Islamic education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District, 2019-2020 academic year. 2) Implementation of school principal management in improving the professionalism of Islamic Education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District, Academic Year 2019-2020. 3) Supporting and inhibiting factors for school principals in improving the professionalism of Islamic Education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District, Academic Year 2019-2020. The subjects of this study were the principal and teachers of SMP Muhammdiyah Simpang Empat, Tangaran District, Academic Year 2019-2020. To obtain data related to the research focus, the researcher conducted interviews, observation and documentation using interview guidelines, observation guidelines using a camera and a tape recorder as data collection tools. The data analysis technique used is qualitative data analysis. In this study, researchers used two techniques, namely: 1) Triangulation Technique, 2) Member Check Technique. The results of the study can be concluded: 1) The principal management plan in improving the professionalism of Islamic Education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District, Academic Year 2019-2020, namely the principal makes a professional program for Islamic Education teachers, the principal makes teaching regulations for PAI teachers, the principal gives an award To teachers who excel, the principal recommends PAI teachers to take certification. 2) Implementation of school principal management in improving the professionalism of Islamic Education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District for the 2019-2020 academic year was carried out by the principal preparing briefing material for PAI teachers, the principal held training for PAI teachers, the principal held supervision of PAI teachers, school principals provide guidance in terms of learning administration. 3) Supporting and inhibiting factors for school principals in improving the professionalism of Islamic Education teachers at SMP Muhammdiyah Simpang Empat, Tangaran District, Academic Year 2019-2020, namely: Supporting Factors; The school principal recommends PAI teachers to take part in the certification program. The school principal briefs PAI teachers. The principal of the school gives awards to outstanding teachers. Obstacle factor; There are still PAI teachers who are not yet undergraduate. There are some teachers who do not respond to teacher professionalism so that the school principal program does not run.